Culture wars - Eagleton, Terry (Primerjalna književnost, 2000)
The crisis of the notion of culture is today evident in the conflict between universalism and particularism, between notions concerning the normative-aesthetic and the antropological-descriptive. The author outlines the historical reasons which, in the post-modern era, have led to a conflict between western universalism and other cultures of the world, and to the complex relations between cultural industry, postžmodernist relativity, the political functionalisation of high culture and the plurality of the politics of identity. He advocates the revalorisation of a radical extensiveness of the universalistic idea of culture of the Enlightenment.
Keywords: kulturologija; filozofija kulture; kulturni sistemi; univerzalizem